Determination of wear resistance and wear mechanisms of HVAF coat-ings based on Ni-Al composition depending on the technological modes of their deposition - Dovhal, A.G.; Pryimak, L.B.; Trofimov, I.I. (Problems of Tribology, 2020)
Presented studies are related to the spheres of aviation and machine-building. World aviation technology experience has accumulated a huge amount of statistical material on the failure airborne systems and ground equipment due to the increased level of parts wear. That is why the issue of research and improvement of anti-wear properties aeronautical parts is one the components when considering the priority directions of ensuring the reliability of operation motor vehicles and friction units. The Ni3Al coating has been deposited on the medium carbon steel using high velocity air fuel deposition. It has been established that it is very sensible for modes of coating deposition and different chemical phenomenon have been detected. The structure of the obtained coating has been thoroughly researched on the electronic microscope. The obtained coating has been tested on the friction bench modeling the fretting process that is taking place in the couple of locking devices of self-propelled passengers stairs. The coating has also corrosion protection. The friction surfaces have been investigated on the electronic microscope and the wear mechanisms have been established. The optimal modes of the HVAF coting deposition from the viewpoint of wear resistance have been detected